Yayasan Metafisika untuk Sains dan Teknologi: Asas Metafisika untuk Sains dan Teknologi - Wirman, Metsra (Jurnal Filsafat Indonesia, 2025)
Some aspects of humanities and modern science that oppose to religion are deeply rooted in a particular metaphysical worldview. The problem is not just in the outcomes produced by modern science, but in the underlying metaphysical assumptions that form the basis of modern science. The objective of this study was to determine that metaphysical foundations could support science and technology, offering insights into how religion and technology interact. The present research employed a qualitative strategy, relying on a literature review and the analysis was by semantic content analysis. The findings reveal that each civilization develops its own metaphysical system, which in turn shapes its unique worldview. These differences came from how each culture perceives reality and assigns value to it. In conclusion, the paper emphasizes to restore a comprehensive metaphysical system that could clarify various levels of reality and presenting the anatomy of being, in its multiple grades and sÉtates